HUBUNGAN TINDAKAN KEMOTERAPI DENGAN KEJADIAN NYERI OTOT PADA PASIEN KANKER PAYUDARA DI RSU SEMBIRING - Meta Rosaulina; Zuliawati Zuliawati (Fakultas Keperawatan Institut Kesehatan Deli Husada, 2022)
Breast cancer is an abnormal cell division in the breast that cannot be controlled so that it spreads quickly. Pain is a factor that contributes to the emergence of fatigue in cancer patients, and has the potential for treatment. Chronic pain is a major healthcare problem for patients with cancer and a major treatment for cancer. Patients will often feel pain during illness or after following chemotherapy. This study aims to determine the relationship between chemotherapy actions and the incidence of muscle pain in breast cancer patients at Sembiring Deli Tua Hospital in 2022. This study used quantitative correlation using a cross sectional approach, the number of samples in this study was 30 people with total side technique. , data collection using research instruments, for independent variables using medical records, and the dependent variable using a Numeric Rating Scale (NRS) questionnaire and observation sheets. The results showed that from 30 respondents. Based on the results of statistical test analysis using the Chi square test with a p-value of 0.028, the p value <0.05. These results indicate that Ha is accepted. Thus, it can be concluded that there is a significant relationship between chemotherapy action and the incidence of muscle pain in breast cancer patients at Sembiring General Hospital Deli Tua in 2022.